The Effect of Gender on Job Satisfaction of Academic Staff in Malaysian Public Universities - Aida Mehrad, Hanina Halimatussadiah Ma’rof Bin Redzuan, Haslinda Abdullah (Universitas Ahmad Dahlan, 2015)
AbstractBased on last due decades, job satisfaction assumed as one of the imperative organizational factors that has great role among staff at workplace;Â furthermore,focusing on this important factor and finding effective items that impact on the level of job satisfaction is very essential. The main purpose of this research is to examine the relationship between gender and job satisfaction of academic staff at public universities in Malaysia. The Job Descriptive Index inventory (JDI) was used to measures five dimensions of job satisfaction among academic staff. The data of this research taken from440 academic staff were occupied in Malaysian public universities. The findings illustrated there is a significant relationship between supervision as one of the dimension of job satisfaction and gender that analyzed by t-test.Key word: Gender, Job Satisfaction, Academic Staff, University